Síntese e funcionalização de azóis via formação de ligações carbono – carbono e carbono – nitrogênio - Wiethan, Carson Wanderley (2017)
This work describes the synthesis and functionalization of azoles employing different methodologies, based on organometallic catalysis or not. Firstly, we disclose the synthesis tetra-substituted 5-trifluoromethyl pyrazoles via sequential halogenation of 5-trifluoromethyl pyrazoles and palladium-catalyzed carbon–carbon and carbon–nitrogen cross-coupling reactions employing organozinc reagents and amines as coupling partners, respectively. This work allowed to achieve new pyrazolic systems in moderated to good yields. Posteriorly, we show the synthesis of 1,3-di(hetero)aryl indazoles exploring the complementary catalytic activity of nickel and copper complexes. We commenced this study evaluating different nickel pre-catalysts to perform the intramolecular amination of unprotected 2-chlorophenyl hydrazones. In a second moment, we described the N-(hetero)arylation of the in situ generated NH indazoles, using a simple catalytic system based on copper/DMEDA. This sequential one-pot fashion procedure allowed the achievement of several 1,3-di(hetero)aryl indazoles in moderate to good yields. Lastly, we disclose the formation of pyrazolo[1,5-a]quinoxalin-4(5H)-ones by the reaction between ethyl 1-(2-chlorophenyl)-1H-pyrazole-5-carboxylate and primary amines. The one-pot methodology undergoes by two sequential reactional pathways: i) amidation of the ester moiety attached to the pyrazole ring, and ii) intramolecular cyclization via nucleophilic aromatic substitution. This synthetic approach proved to be efficient only for primary aliphatic amines, allowing to achieve molecules with different substitution patterns in moderate to good yields. Key-words: Azoles, quinoxalinones, Negishi cross-coupling, Buchwald-Hartwig cross-coupling.